The development and demonstration of a practical methodology for fine particle shape characterisation in minerals processing - Little, Lucy (Centre for Minerals Research, 2017)
Due to continually declining ore grades, increasing mineralogical complexity, and increasing metal demand, models for the design and optimisation of minerals processing operations are of critical importance. These models do not currently incorporate particle shape, which, although rarely quantified, is known to affect numerous unit operations. Automated Scanning Electron Microscopy (Auto-SEM-EDS) is a widely used tool for mineralogical analysis. It also provides an opportunity for simple, quantitative and mineral-specific shape characterisation. Existing mineralogical databases could therefore become useful resources to facilitate the incorporation of shape effects in minerals processing models. A robust Auto-SEM-EDS shape characterisation methodology is required to ensure that the particle shape information in these databases is interpreted appropriately. For this work, a novel methodology for Auto-SEM-EDS shape characterisation was developed that is suitable for the analysis of fine particles (<75 μm). This involved testing the response of various shape descriptors to image resolution, and measurement with different devices and image processing routines. The most widely used shape descriptor in minerals processing, circularity, was found to be highly dependent on both image resolution and image processing settings, making it a poor choice for shape characterisation of fine particles. Roundness and aspect ratio were found to be more robust descriptors. However, in the interest of being able to compare particulate shape measurements across different studies, the precise definition of aspect ratio is important as variation in 'length' and 'width' definitions can significantly impact aspect ratio measurements. The possibility that preferential orientation of particles would introduce bias to the 2-D cross-sectional measurements was also addressed through comparison of roundness distributions measured from orthogonal cross-sections of a particulate sample mounted within a block of resin. The excellent repeatability of these measurements indicated that the particles were randomly orientated, and thus it can be inferred that 2-D measurements of a sufficient number of particles will be directly related to the particulate sample's 3-D properties. Roundness and aspect ratio were then used in conjunction to produce surface frequency distributions that allow for distinction between non-rounded particles that were smooth and elongated and non-rounded particles that were neither elongated nor smooth. Three applications of the shape characterisation methodology developed were then demonstrated, which highlighted some of the potential contributions that this methodology can make towards minerals processing. The applications were all based on a case study of the Upper Group 2 (UG2) Chromitite, a platinum group mineral (PGM) ore of key economic significance to South Africa.